Régimen de insolvencia empresarial: propuesta de unificación de los privilegios concursales para los países miembros de la comunidad andina de naciones. Estado del arte. (2007)
The current context of world’s globalization, opening of borders, business and across-the-bordereconomies in quick evolution, where the commercial transactions acquire a bigger dynamism pushed primarily by the artificial structure of the societies that day by day give origin to more complex legal operations; imposes new challenges to the national legislations that are not prepared to face the demands of the modern trade flows. In cooperation areas or in future integration processes, harmonization and legislative unification regarding Bankruptcy law play a critical role. This requires the countries’ internal legislations to adopt harmonic, modern and efficient regimes that guarantee societies, managers andinvestors, legal security about the development of their business or in case of financial difficulties.